Severe Hepatic Complications of Antituberculous Therapy. (1999) - Turner, Mark O; Elwood, R Kevin
Abstract : Hepatotoxicity from antituberculous therapy is well described, but fortunately severe complications are rare. The optimal methods of monitoring for significant hepatotoxicity while on treatment are uncertain. Some authorities recommend measuring liver enzymes only if symptoms develop, whereas others recommend regular liver enzyme monitoring throughout the course of therapy. In British Columbia, from 1990 to 1997, 2624 active and approximately 8000 chemoprophylaxis cases have been treated, but only two severe complications directly related to antituberculous therapy have occurred. A 33-year-old male developed fulminant hepatic failure seven months after starting isoniazid chemoprophylaxis and required a liver transplant. The other patient died from hepatic failure that developed in the first month of triple-drug therapy for proven active pulmonary tuberculosis. The early and late onset of hepatic failure associated with antituberculous therapy in these cases underline the difficulties in identifying a monitoring protocol that will totally negate the risk of severe complications.